Hubungan Psychological Capital Dengan Kepuasan Kerja Pada Anggota Polri Yang Sedang Mengikuti Pendidikan Di Perguruan Tinggi Ilmu Kepolisian (PTIK) - Aldia Thirzady Hedissa; Iman Sukhirman; Andi Supandi (Universitas Muria Kudus, 2012)
This thesis discusses the relationship between Job Satisfaction PsyCap with the police officers who are following in PTIK education, as the candidates head of police in the future. The study is a quantitative research also aims to see the picture PsyCap and job satisfaction in participants. The results of the study indicate that the picture PsyCap and job satisfaction in police officers who were to attend a PTIK are at moderate levels; there is arelationship between job satisfaction PsyCap; and PsyCap only twodimensions, namely resiliency and optimism related to job satisfaction.